P417 Long-term deep remission after adalimumab discontinuation in Crohn's disease patients. (27th May 2021) - Melotti, L; Rizzello, F; Calabrese, C; Dussias, N; Gionchetti, P
Abstract: Background: Adalimumab is a safe and effective drug in treatment of Crohn's Disease (CD). Current literature is not definitive regarding an exact timing for treatment withdrawal and disease relapses after drug discontinuation. Methods: We conducted a single-centre, retrospective, observational cohort study involving patients affected by Crohn's Disease (CD) treated with adalimumab. Of 575 patients treated with adalimumab for CD, 149 patients suspended treatment for stable deep remission (clinical steroid-free, biochemical, endoscopic remission defined as mucosal healing). Of these, 126 have a minimum follow up of 4 years, the other 23 where lost or finished the follow-up. Patients were assessed clinically, laboratoristically and endoscopically for 4 years. Relapse was defined as clinical (HBI > 4) and biochemical (PCR > 0.5 mg/dL). Results: Of the 126 patients with 4 years follow-up, 64 (51%) maintained deep remission during the 4 year follow-up period. Of these, 38 (59%) were on exit-therapy with thiopurines. Twenty-seven patients (18%) had relapsed by year 1, 24 (18%) by year 2, 8 (6%) by year 3, and 1 (0.8%) by year 4. Relapses needed surgical therapy in 9 (15%) cases, whereas 36 (60%) were retreated with adalimumab and 4 (7%) with another biologic agent. The remaining 11 patients (18%) were treated only with a course of steroids. Conclusion: Patients who suspend treatment with adalimumab for stable deep remission maintain remission in the long term in approximately half of cases. The majority of relapses occur in the first 24 months after discontinuation.